ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI ULANG MASYARAKAT MUSLIM KOTA MALANG TERHADAP MIE GACOAN - Fadhillah, Muhammad Ayyub; Noor, Iswan (Islamic Economics and finance in Focus, 2024)
Mie Gacoan is a spicy noodle restaurant that was founded in early 2016. Mie Gacoan is now spread in almost all big cities in Indonesia. One of them is Malang City, where Mie Gacoan was founded. In recent years, Mie Gacoan has always been busy with buyers, either eating on the spot or buying via the online application. This research aims to determine the factors that influence Muslim consumers repurchase interest in Mie Gacoan in Malang City using the variables halal certification, EWOM and product quality. This research used a questionnaire by taking 153 respondents. The sampling technique used is a probability sampling technique with a simple random sampling method. The analysis technique used is multiple linear regression analysis. The results of the T test state that the EWOM variable and product quality partially have a positive and significant effect on repurchase interest. Meanwhile, halal certification does not have a significant effect on repurchase intention. The results of the F test show that halal certification, e-wom, and product quality simultaneously influence repurchase interest.